A Switched Approach to Image-Based Stabilization for Nonholonomic Mobile Robots with Field-of-View Constraints - Yao Huang (MDPI AG, 2021)
This paper presents a switched visual servoing strategy for maneuvering the nonholonomic mobile robot to the desired configuration while keeping the tracked image points in the vision of the camera. Firstly, a pure backward motion and a pure rotational motion are applied to the mobile robot in succession. Thus, the principle point and the scaled focal length in x direction of the camera are identified through the visual feedback from a fixed onboard camera. Secondly, the identified parameters are used to build the system model in polar-coordinate representation. Then an adaptive non-smooth controller is designed to maneuver the mobile robot to the desired configuration under the nonholonomic constraint. And a switched strategy which consists of two image-based controllers is utilized for keeping the features in the field-of-view. Simulation results are presented to validate the effectiveness of the proposed approach.